Pengaruh Penerapan Metode Talaqqi Terhadap Kemampuan Tahsin Siswa Pada Mata Pelajaran Baca Tulis Qur’an - Fauziah, Hapsah; Komariah, Ria (STAI Al-Musaddadiyah Garut, 2023)
The ability to improve Qur'anic reading (tahsin) is crucial in the learning process of Qur'anic literacy (BTQ - Baca Tulis al-Qur’an) for students. Currently, many students have not achieved adequate tahsin skills, as evidenced by their learning outcomes. The Talaqqi method in BTQ instruction is a promising approach that can train students to read the Qur'an according to the rules of tajweed and makharijul huruf, thereby enhancing their tahsin skills. This study aims to describe: (1) the implementation of the Talaqqi Method in Qur'anic literacy instruction at SD IT Lisanul Arab, (2) the tahsin skills of students, and (3) the impact of the Talaqqi Method on students' tahsin abilities. This research adopts a quantitative approach with a descriptive correlational method. Data collection techniques include documentation studies, questionnaires, pre-tests, and other relevant methods. Data processing is conducted through statistical analysis using the